In situ calibration of meteorological sensor in Himalayan high mountain environment. (11th November 2015) - Merlone, Andrea; Roggero, Guido; Verza, Gian Pietro
ABSTRACT: A dedicated facility for in situ calibration of weather stations has been installed in the Everest Pyramid Laboratory/Observatory at an altitude of 5050 m in the Khumbu Valley, on the Nepalese side of Mount Everest. This highest metrology laboratory in the world represents a fruitful collaboration between metrological and environmental sciences. The common goal is the improvement of data quality and the reliability of climate monitoring. High altitude extreme environmental observations are of high scientific relevancy, underlining the advantages of performing in situ instrument calibration to make measurements fully traceable to standards. In establishing such a laboratory in extreme conditions, the involved staff had to face several challenges: weight of the system components for the eventual transport by human porters, modification to 'off the shelf equipment', special procedures and optimization of power request, reduced room available, properties of fluids at high altitude and many more. The work and the mission reported are tasks of the MeteoMet project, which are presented here together with the organizations involved. The calibration chamber, the calibration procedure and the results of the first calibration campaign are then presented with full uncertainty analysis. The capabilities achieved, together with the trained staff and dedicated procedures, now allow calibration and checking of the instruments positioned all along the Khumbu Valley, up to the Everest South Col at 8000 m, more frequently, with less difficulties and with reduced loss of time. Future plans include the extension of the calibration capabilities to soil, ice, permafrost and lake water temperature sensors.